Malpils Manor: architecture, cultural and historical developments. Second half of the 18th century – first quarter of the 21st century - Zilgalvis, Jānis (Landscape Architecture and Art, 2022)
The history of construction of the Malpils Manor (Lemburg), which is closely linked to cultural history, has developed over a long period of time – from the second half of the 18th century to the present day. It has seen its heyday and its down times, when it was burnt down and destroyed. However, its fate was not sealed to disappear from the face of the earth, as has happened to many similar buildings in other Latvian manors. The manor house has blossomed again in all its glory, and is awaiting everyone who wants to spend some time in a well-tended historic and truly noble environment. However, the study of the manor in its broad cultural and historical context is still relevant.